2000
DOI: 10.1159/000018471
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Kinetic Evidence for Increased Recruitment of Cycling Epidermal Cells in Psoriasis: The Ratio of Histone and Ki-67 Antigen Expression Is Constant

Abstract: Background: One of the hallmarks of the psoriatic plaque is increased epidermal proliferation. Whether this is the result of an increased recruitment of cycling epidermal cells or a decrease in cell cycle time has been a matter of debate for years. Objective: Calculating cell-kinetic information from the number of S phase cells in psoriasis by in situ hybridisation using a histone probe and the number of cycling epidermal cells by immunohistochemistry using the MIB-1 antibody. Methods: Immunohistochemistry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Excessive expansion of the TA cells compartment has been recently described in psoriatic skin (77), where a defect in TA subpopulation seems to account for the epidermal abnormalities observed in the disease (78). In addition, in silico studies have simulated psoriasis by altering the TA cells (79), and psoriatic TA cells are more advanced in their life cycle than their normal counterpart (80).…”
Section: P75ntr and Epidermal Homeostasismentioning
confidence: 99%
“…Excessive expansion of the TA cells compartment has been recently described in psoriatic skin (77), where a defect in TA subpopulation seems to account for the epidermal abnormalities observed in the disease (78). In addition, in silico studies have simulated psoriasis by altering the TA cells (79), and psoriatic TA cells are more advanced in their life cycle than their normal counterpart (80).…”
Section: P75ntr and Epidermal Homeostasismentioning
confidence: 99%
“…In the current view, plaque psoriasis is a T-cell-mediated skin disorder, characterized by epidermal hyperproliferation and an aberrantly differentiated epidermis [1,2,3,4,5]. Activated (CD25+) memory effector (CD45RO+) T cells of the T-helper (CD4+) or the cytotoxic (CD8+) subset reside locally in lesional psoriatic skin, in both the dermis and the epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…Early mathematical models describing cell renewal in psoriasis had demonstrated that the typical psoriatic tissue architecture is based not only on an increased turnover rate in the germinative cell, but also on a defect in cells transiting to the more differentiated state. More recently, Castelijns et al, 39 using kinetics parameters, have proposed that epidermal abnormalities in psoriasis are due to a defect in the transitamplifying compartment, rather than to a reduction in the cell cycle time. TA cells in psoriasis are thought to be kept in a prolonged proliferative state, which would account for an increased number of cell division, with no reduction of cell cycle time.…”
mentioning
confidence: 99%